2014
DOI: 10.1089/thy.2013.0121
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcitonin May Falsely Estimate Tumor Burden in Chronic Hypercalcemia: A Case of Prostatic and Multiple Bone Metastases from Medullary Thyroid Cancer

Abstract: A chronic hypercalcemic state may exhaust Ct reserves and diminish the Ct response to an acute intravenous calcium injection. Therefore, the Ct level of a patient in a hypercalcemic state should be carefully interpreted. To our knowledge, this is the first reported case in the literature in which serum Ct levels were not significantly increased when associated with hypercalcemia, and an MTC metastasis to the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…emphasized that preoperative serum calcitonin levels of more than 20, 50, and 200 pg/mL are associated with ipsilateral central and lateral LNM, contralateral central LNM, and contralateral lateral LNM, respectively ( 12 ). However, previous studies have confirmed that preoperative serum calcitonin levels are related to many factors, such as the diameter of the primary tumor and the malignancy of the tumor ( 19 21 ). Even when serum calcitonin levels are hundreds of times higher than the upper limit of normal, patients may not benefit from lateral neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…emphasized that preoperative serum calcitonin levels of more than 20, 50, and 200 pg/mL are associated with ipsilateral central and lateral LNM, contralateral central LNM, and contralateral lateral LNM, respectively ( 12 ). However, previous studies have confirmed that preoperative serum calcitonin levels are related to many factors, such as the diameter of the primary tumor and the malignancy of the tumor ( 19 21 ). Even when serum calcitonin levels are hundreds of times higher than the upper limit of normal, patients may not benefit from lateral neck dissection.…”
Section: Discussionmentioning
confidence: 99%